The End of the Old Order in Rural Europe - Blum, Jerome (Book collections on Project MUSE., 2017)
The eighteenth and nineteenth centuries witnessed the transformation of the old rural order to the modern class society. While historians have studied this transition as it occurred in individual countries, Jerome Blum offers the first view of it as a European experience tha transcended political frontiers. Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.